2011
DOI: 10.1108/17410381111134473
|View full text |Cite
|
Sign up to set email alerts
|

A systems engineering approach to supply chain auditing

Abstract: Purpose -The purpose of this paper is to discuss the theoretical foundations, development, and application of the quick scan audit methodology (QSAM) for comparative evaluation of supply chains via uncertainty codification and material flow assessment. Design/methodology/approach -Charts the evolution of QSAM via the Parnaby concept of a manufacturing system leading to a control model representation of a value stream. Monitoring in process and critical interface material and information flows provide the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…An important feature of the QSAM is that the issues identified during the audit process are analysed using systems thinking in order to yield a cause-effect diagram (Naim et al, 2002). The theoretical basis for this QSAM analysis is system-engineering principles which involve feedback thinking and process control theory (Parnaby, 1979;Childerhouse and Towill, 2011a), as illustrated in Figure 1. Consequently, those issues encountered by a business in the supply chain are categorised into four uncertainty areas, namely supply side, process side, demand side and control side.…”
Section: Quick Scan Audit Methodology (Qsam)mentioning
confidence: 99%
See 1 more Smart Citation
“…An important feature of the QSAM is that the issues identified during the audit process are analysed using systems thinking in order to yield a cause-effect diagram (Naim et al, 2002). The theoretical basis for this QSAM analysis is system-engineering principles which involve feedback thinking and process control theory (Parnaby, 1979;Childerhouse and Towill, 2011a), as illustrated in Figure 1. Consequently, those issues encountered by a business in the supply chain are categorised into four uncertainty areas, namely supply side, process side, demand side and control side.…”
Section: Quick Scan Audit Methodology (Qsam)mentioning
confidence: 99%
“…Through a case study, they have shown how the implementation of the QSAM into the design, development and early stage implementation of a LSS project has provided a simple yet effective method to achieving improvements in the project performance. While identifying opportunities for improvement in many aspects of businesses (Naim et al, 2002;Childerhouse et al, 2010;Atilgan and McCullen, 2011;Childerhouse and Towill, 2011a), the QSAM also yields rich empirical data to test and further investigate various issues including supply chain integration, time compression, the bullwhip effect and simplified material flow (Potter et al, 2009;Childerhouse and Towill, 2011b).…”
Section: Evolution and Adaptation Of Qsammentioning
confidence: 99%
“…An example is the generation of bullwhip across the supplier/original equipment manufacturer interface (Childerhouse, Disney, & Towill, 2008). Further explanation of the QSAM Balanced Score card can be found in Childerhouse and Towill (2011).…”
Section: A Mixed-methods Approach To Supply Chain Researchmentioning
confidence: 99%
“…A number of different tools have been developed using different concepts and scope (Table 1). The guidance of the uncertainty circle diagram is the focus of many applications, for example Quick Scan Audit Methodology (QSAM) (Naim et al 2002;Childerhouse and Towill 2011;Böhme et al 2013Böhme et al , 2016. QSAM (Naim et al 2002) is an auditing tool that is based on systems engineering concepts where primary data sources are collected for understanding four sources of uncertainty (supply side, demand side, process side and control side).…”
Section: Background Researchmentioning
confidence: 99%